(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research studies the link between identity, resistance, and cultural conciliation in Maya Angelou’s renowned poem "Still I Rise." Drawing from Homi K. Bhabha’s theoretical agenda, mainly his concepts of hybridity and mimicry, the current study scrutinizes how Angelou’s poem works as a principal assertion of resilience against colonialism and overbearing constructions. By doing a detailed inspection of the poem, the article argues the ways in which Angelou exercises an impertinent voice that goes beyond the binaries of oppressor and oppressed, forming a space for a hybrid identity that celebrates both African legacy and the present self-assertion. The exploration discusses the mechanisms of mimicry as a system for resistance, where the speaker’s self-possessed restoration of power dislocates conformist narratives of dominance. By affirming her right to rise notwithstanding historical and systemic command, Angelou displays the convolutions of postcolonial identity, signifying how insubordination can arise from the very structures that wish to downgrade. Furthermore, this research places "Still I Rise" in the grander outline of postcolonial discourse, stressing the poem’s importance in the modern arguments of race, gender, and empowerment. In conclusion, this exploration discloses that Angelou’s verse is not only a personal legalization but a collective bonding call for downgraded voices. It features the inference of hybridity and mimicry as tools for reclaiming intervention and identity in a world affected by colonial histories.